Occurrence of Fungi in the Primary Film on Glass Slides Submerged in Cochin Backwaters - B., Meenakumari; Gupta, RANU; N., Balakrishnan Nair (Fishery Technology, 2025)
Occurrence of fungal mycelia was observed on the glass slides after 48 h of submersion in the Cochin backwaters. The fungus Curularia lunata (Wakker) Boedijn was found throughout the year while Aspergillus terreus Thom., Trichoderma pseudokoningii Rifas and Phomopsis spp. were found only during the low saline period prevailing in the monsoon season. The presence of fungi in the primary film is of importance in the context of its probable role in the biochemistry of the slime film and also in promoting corrosion of metal substrates.